Enhancing Livelihoods through Digital Finance: A Study on the Impact of FinTech Adoption on the Financial Performance of Hawkers - Kishore Kunal; K. R. Ramprakash; Arun Prasad R (Qubahan Academic Journal)
This study examines the determinants driving FinTech adoption among hawkers in Tamil Nadu and evaluates the resulting impact on their financial performance. Using a framework based on the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT), along with service quality attributes, this study investigates the factors influencing digital payment adoption. A sample of 1,200 hawkers was surveyed across eight districts in Tamil Nadu through stratified random sampling. The relationships between constructs were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results demonstrate that ease of use (β = 0.23), security (β = 0.37), and social influence (β = 0.077) have a significant positive impact on digital payment adoption among hawkers. Conversely, responsiveness and perceived usefulness did not show a significant effect. Adoption of digital payments led to an average increase of 15% in daily sales, with variations in financial outcomes based on age and education levels. The study also confirms the model’s predictive relevance in assessing the financial impacts of FinTech adoption for informal entrepreneurs. These findings offer actionable insights for FinTech companies and policymakers focused on the informal economy. To enhance FinTech adoption, emphasis should be placed on user-friendly, secure platforms and community-driven campaigns that leverage social influence, which are essential to fostering financial inclusion and economic development. This study contributes to the limited literature on FinTech adoption in the informal economy by providing empirical evidence on the factors influencing digital payment adoption among hawkers and the impact on their financial performance. Through advanced statistical analysis, the study delivers robust findings to inform policy and practice.